COMPANY PERFORMANCE AND STOCK RETURNS IN INDONESIA CONSTRUCTION COMPANIES - Yolanda Paskalin Dudung Sorreng; Eriana Kartadjumena (SEAN Institute, 2023)
The purpose of this analysis was to identify the best and worst performing IDX construction sector businesses from 2016 through 2021 in terms of stock return performance. During the carrying period, the company's performance was evaluated using the profitability ratio, measured by return on equity, the solvency ratio, measured by debt to equity, the market ratio, measured by price to book value, and the beta value. Annual reports filed with the Indonesia Stock Exchange and Pefindo Beta Stock provide the information used here. Quantitative techniques including imbalanced panel data analysis were applied in this study. Uneven statistics from 109 annual reports from 20 businesses in the construction sector listed on the This analysis focused on the Indonesia Stock Market. Return on equity was found to have a statistically significant positive influence on stock returns, but debt to equity ratio, price to book value, and beta risk all failed to make a statistically meaningful impact. The findings of this study provide a useful resource for anybody considering making a financial investment in a company listed on the Indonesia Stock Exchange that operates in the construction industry. In addition, please find an attached appraisal of the company's financial performance based on fundamental research.